2013
DOI: 10.1111/joms.12037
|View full text |Cite
|
Sign up to set email alerts
|

Why Do I Feel Valued and Why Do I Contribute? A Relational Approach to Employee's Organization‐Based Self‐Esteem and Job Performance

Abstract: Drawing on the relational perspective and self-consistency theory, we theorize how relationships involving work-centric, off-work-centric, and/or personal components can affect an employee's organization-based self-esteem and job performance in Chinese organizational contexts. Matched data were collected from a multi-source sample that included 219 employee-supervisor dyads from a Chinese bank. Results based on hierarchical regression analyses reveal that a high-quality relationship with a supervisor through w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 70 publications
3
79
2
Order By: Relevance
“…Second, we did not consider other types of interpersonal relationships. We are unsure whether the impact of mentorship quality is still unique and significant when other positive interpersonal connections (such as supervisor support) are considered (Liu et al, ). Although previous studies have demonstrated the collaboration of different supportive interpersonal ties (Dobrow et al, ; Murphy & Kram, ), additional research is needed to measure mentorship quality alongside other types of interpersonal connections and to further confirm the independent effects of mentorship quality.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not consider other types of interpersonal relationships. We are unsure whether the impact of mentorship quality is still unique and significant when other positive interpersonal connections (such as supervisor support) are considered (Liu et al, ). Although previous studies have demonstrated the collaboration of different supportive interpersonal ties (Dobrow et al, ; Murphy & Kram, ), additional research is needed to measure mentorship quality alongside other types of interpersonal connections and to further confirm the independent effects of mentorship quality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown empirically that having informal connections with supervisors outside the work domain has positive effects on subordinates' outcomes in the work domain, such as enhancing their social and psychological capital, promoting their organizational self‐esteem (Liu, Hui, Lee, & Chen, ), and enabling them to have more open dialogue with the leader (Chen & Tjosvold, ). These findings support our argument that the effect of LMG‐P developed in the private domain can spill over to the work domain.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Relationships with one's supervisor and colleagues may be the most important sources for an overqualified employee's self‐concept, especially in Chinese culture, which is characterized by collectivism (Chen, Chen, & Huang, ). A number of studies have examined and found support for the notion that relationships can affect individuals' self‐concept and work performance (Liu, Hui, Lee, & Chen, ; Zhao, Kessel, & Kratzer, ). We predict that the interaction between perceived overqualification and relationships determines employee's self‐concept and performance.…”
Section: Introductionmentioning
confidence: 99%